Correlation between the Parameters of Signal‐Averaged ECG and Two‐Dimensional Echocardiography in Patients with Arrhythmogenic Right Ventricular Cardiomyopathy - Park, Yongwhi (Ann Noninvasive Electrocardiol, 2009)
Background: The correlation between parameters of two‐dimensional echocardiography and signal‐averaged ECG (SAECG) in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) is not known well. Methods: Thirty‐three patients (13 females, 40.3 ± 14.4 years old) were included in this study. Both the right and left ventricular dimensions and systolic function were assessed with two‐dimensional echocardiography. The SAECG was performed with high‐gain amplification and filtered using bidirectional Butterworth filters between 40 and 250 Hz. We evaluated the correlation between the parameters of the SAECG and two‐dimensional echocardiography. Results: The right ventricular (RV) outflow tract was the most frequently (n = 18, 54%) involved segment. Six (18%) patients had only mildly decreased RV systolic function. All the other patients had normal RV systolic function. Although localized left ventricular wall motion abnormalities were observed in 14 (42%) patients, the left ventricular ejection fraction was normal in most (n = 32, 97%). Late potentials were positive in 22 (63%) patients. There was no significant correlation between parameters of the SAECG and two‐dimensional echocardiography for the entire patient population. Conclusions: The SAECG parameters exhibited no correlation to any of two‐dimensional echocardiography parameters in the patients with ARVC. Fragmented electrical activity may develop with no significant relation to the anatomical changes in the patients with ARVC.